Noun in “ Silly Questions” - Zainuddin Zainuddin (English Education : English Journal for Teaching and Learning, 2019)
The researcher focuses the study on Noun for “Silly Questions” in English is Fun (book). The research is done through descriptive qualitative, in which the aims of the research are to describe Noun for “Silly Questions” in English is Fun (book), which is based on kinds of Concrete Noun; Proper Noun, Common Noun, Material Noun, and Collective Noun. Additionally, here the researcher tries to determine the dominant use of kinds of Concrete Noun. Consequently, the researcher takes “Silly Questions” for primary data, and then some related Journals and books about Noun. Furthermore, the researcher uses content analysis method for analyzing the data. There the technique of analyzing the data; Reading 15 Silly Questions and its answers, signing kinds of Concrete Noun in the 15 Silly Questions, and then giving found kinds of Concrete Noun explanations. Finally, having conclusion of overall discussion. In conclusion, there are 43 Concrete Nouns; They are eight Proper Nouns, 26 Common Nouns, one Material Noun, and eight Collective Nouns for 15 Silly Questions in English is Fun (book) as the result of the research.